Medievalism, Modernity and Memory: Cropthorne Church, 1892–1910. (2nd January 2016) - Ferry, Emma
Abstract: 'An old church is so common and so familiar an object that we are often in danger of forgetting its value...' George Gilbert Scott (1811-78) Recorded in the Domesday Survey for Worcestershire (1086), the Church of St. Michael in Cropthorne, Worcestershire is an ancient building with a rich history. Drawing on surviving manuscript and visual sources, this article examines the repairs, restoration and refurbishments made to the interior of St. Michael's between 1890 and 1910. This was a period in which the ownership of the village shifted from the Anglican Church to private patronage and a time which witnessed many changes to the fabric of the building; notably the extensive refurbishments carried out to the chancel in 1894 by Francis Holland, the Lord of the Manor and the restoration of the rest of Cropthorne church which took more than eighteen years to complete. Highlighting the significance of the Church in rural areas as a place for personal and community memory, this article will consider how these changes to a sacred space used for communal worship were linked to the social changes experienced by the rural community that worshipped within it: moving beyond a purely architectural survey of the building, it will identify the agents of these changes; the processes involved in accomplishing them; and, responses to these alterations. Consequently, the alterations and additions to the interior of St. Michael's made at the instigation and expense both of the Holland Family of Cropthorne Court and the people of Cropthorne will be analyzed in the context of the changing religious, technological, social, economic and political conditions of the period, which include the effects of the Agricultural Depression and the devastating impact of war.